(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2021)
Milk is a nutrient-rich liquid food for human and animals. However, owing to its complex biochemical structure and high water activity, it serves as an outstanding microorganism growth medium under suitable conditions. People in Bangladesh’s coastal areas have a lifestyle and tradition that includes drinking raw milk for nutrition or as an energy drink, which presents a health risk to them. The present cross-sectional study was carried out to determine the reasons for drinking raw milk in coastal areas, as well as the public health impact of doing so. A total of 100 respondents were interviewed and subsequently, milk samples were collected for quality testing through methylene blue reduction test (MBRT). Among 100 respondent 70 were consumers and 30 were farmers. Results showed that the samples of farmers were better than that of consumers. The majority of raw milk consumers were male who thought raw milk was more nutritious than heat-treated milk. Furthermore, the majority of them were professionally engaged in farming. Both consumers and farmers had less educational qualifications, managed their cattle in dirty environments, practiced extensive grazing system on communal grazing areas and around one fourth of them vaccinated their animals. Furthermore, the findings revealed that 40% of respondents were between the ages of 35 and 45, with 62% reporting no health complications as a result of drinking raw milk and the remainder reporting mainly gastrointestinal problems. According to the findings of this report, the quality of raw cow milk was poor; unhygienic practices and poor animal husbandry at farm level predisposed farmers, consumers and the public to risk of contracting milk-borne infections and associated bacterial resistances. It is recommended that veterinarians, extension officers and all stakeholders should play their roles in ensuring safe quality milk supply to consumers. Asian Australas. J. Biosci. Biotechnol. 2021, 6 (1), 10-18